Trichopilia x ramonensis - Darstellung einer Naturhybride aus Costa Rica - Morales Sánchez, Carlos (2003)
The natural hybrid Trichopilia x ramonensis (T. marginata x T. suavis) from the San Ramón region of Costa Rica is here presented and illustrated. Its name was validated in 2002, many years after its first mention in the literature.